Model organism databases: essential resources that need the support of both funders and users. Issue 1 (December 2016) - Oliver, Stephen; Lock, Antonia; Harris, Midori; Nurse, Paul; Wood, Valerie
Abstract Modern biomedical research depends critically on access to databases that house and disseminate genetic, genomic, molecular, and cell biological knowledge. Even as the explosion of available genome sequences and associated genome-scale data continues apace, the sustainability of professionally maintained biological databases is under threat due to policy changes by major funding agencies. Here, we focus on model organism databases to demonstrate the myriad ways in which biological databases not only act as repositories but actively facilitate advances in research. We present data that show that reducing financial support to model organism databases could prove to be not just scientifically, but also economically, unsound.